2009
DOI: 10.1002/gcc.20656
|View full text |Cite
|
Sign up to set email alerts
|

Genomic instability in giant cell tumor of bone. A study of 52 cases using DNA ploidy, relocalization FISH, and array‐CGH analysis

Abstract: Genetic instability in relation to clinical behavior was studied in 52 cases of giant cell tumor of bone (GCTB). Ploidy was determined in the mononuclear cell population by using native cell smears and image cytometry. A relocalization technique allowed fluorescent in situ hybridization (FISH) analysis of CD68-negative neoplastic cells for numerical changes of chromosomes X, 3, 4, 6, 11, and telomeric association on 11p. Genome-wide alterations were tested using array comparative genomic hybridization (array-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 41 publications
5
25
0
Order By: Relevance
“…Eusomic polysomy has been seen in several tetraploid nonrecurrent cases, and balanced aneusomy has been found more frequently in diploid recurrent than in diploid nonrecurrent cases. These findings suggest that chromosomal abnormalities superimposed on telomeric associations might be responsible for the aggressive behavior of GCTB [31]. The expression of proteins involved in cell cycle regulation/oncogenesis, such as p53, p63, ki-67, cyclinD1, or Bcl-2, are not predictive for the clinical behaviour of GCTB [32].…”
Section: Prognosismentioning
confidence: 82%
“…Eusomic polysomy has been seen in several tetraploid nonrecurrent cases, and balanced aneusomy has been found more frequently in diploid recurrent than in diploid nonrecurrent cases. These findings suggest that chromosomal abnormalities superimposed on telomeric associations might be responsible for the aggressive behavior of GCTB [31]. The expression of proteins involved in cell cycle regulation/oncogenesis, such as p53, p63, ki-67, cyclinD1, or Bcl-2, are not predictive for the clinical behaviour of GCTB [32].…”
Section: Prognosismentioning
confidence: 82%
“…A p53 mutation has also been reported in bone and soft tissue sarcomas [12]. However, a p53 mutation has rarely been reported in malignant or benign GCT [13,14]. A p53 point mutation as well as p53 overexpression in stromal cells has been reported in a case of recurrent GCT diagnosed as malignant GCT [14].…”
Section: Discussionmentioning
confidence: 97%
“…We have previously shown that random aneusomy is a feature of the CD68-negative mononuclear stromal cell population of giant cell tumour of bone, and that this feature correlates with biological aggressiveness, with chromosomal gain and loss turning into clonal but random genetic aberrations in malignant cases. 2 In this study, we show that there is a strong correlation between chromosomal instability and centrosome amplification, suggesting a possible involvement of the latter in generating chromosomal instability in giant cell tumour of bone. However, relocalization studies and immunocytochemistry, in combination with FISH, showed no association between centrosome amplification and chromosome number alteration, indicating that alternative causative mechanisms are responsible for generating genetic instability in giant cell tumour of bone.…”
Section: Discussionmentioning
confidence: 49%
“…24 Membrane and cytoplasmic expression of CTNNB1, a member of the Wnt signalling pathway, has been observed in giant cell tumour of bone; although the failure of this signalling route (usually with the nuclear accumulation of CTNNB1) is well known to cause aneusomies and tetrasomies, 25 no significant correlation has been observed between CTNNB1 positivity and the degree of aneusomy in giant cell tumour of bone, or between CTNNB1 expression and giant cell tumour of bone recurrence. 2,26 One of the most commonly observed genetic aberrations in giant cell tumour of bone is telomeric association. Telomeric association alone, however, does not have a role in the development of genetic instability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation